Association between multimorbidity and cognitive decline in the elderly population of the Eastern Province, Saudi Arabia - Khalid S. AlHarkan; Adam F. Aldhawyan; Ahmed S. Bahamdan; Yousef D. Alqurashi; Fajar A. Aldulijan; Sarah I. Alsamin; Jood K. Alotaibi; Arwa K. Alumran (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: Cognitive decline affects the quality of life, and dementia affects independence in daily life activities. Multimorbidity in older adults is associated with a higher risk of cognitive impairment. This research aims to study the relationship between cognitive decline and multimorbidity in the elderly population in the Eastern Province, Saudi Arabia. MATERIALS AND METHODS: This cross-sectional research was conducted from July to October 2022 among adults over 60 years. All patients with two or more comorbidities were contacted for a face-to-face interview and cognitive testing to estimate cognitive function by trained family physicians using St. Louis University Mental State Examination. ANOVA and Chi-square test were used to test for statistical significance. Binary logistic regression was used to show the odds of having cognitive impairment and multimorbidity. All tests were performed at 5% level of significance. RESULTS: The study involved 343 individuals; majority (74.1%) aged 60-75 years and were males (67.9%). Hypertension, diabetes, and chronic pain were reported by 56%, 48%, and 44% participants, respectively. Thirty percent participants had 3 or more comorbidities. About 36% had mild neurocognitive disorder and 31.2% had dementia. The results showed that age, gender (female), diabetes, stroke, chronic pain, and multimorbidity were significantly associated with cognitive impairment. In our study, hypertension, coronary artery diseases, depression, and anxiety were not significantly associated with risk of cognitive decline. CONCLUSION: Our study found that multimorbidity is significantly associated with cognitive decline. Controlling comorbidities and preventing risk factors in midlife could help in delaying the progression of the disease.